1996
DOI: 10.1063/1.471009
|View full text |Cite
|
Sign up to set email alerts
|

The photoionization of large pure and doped helium droplets

Abstract: The photoionization of neutral liquid helium droplets (mean particle number 〈N〉=102–107) was studied using synchrotron radiation at photon energies ranging from 15 to 30 eV. Mass spectra as well as total and mass selective ion yields were measured as a function of the photon energy for different droplet sizes. The experiments indicate that ionization occurs not only by a direct process at photon energies above the atomic ionization potential but also at energies below the threshold by an autoionization process… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

18
143
1

Year Published

2007
2007
2022
2022

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 88 publications
(162 citation statements)
references
References 26 publications
18
143
1
Order By: Relevance
“…The importance of Rydberg-like excitations in He droplets below IE(He) has been established in the fluorescence excitation spectra by Möller and co-workers, 53,55 and the role of molecular autoionizing states was first suggested by Fröchtenicht et al 9 to explain the onset of photoionization below IE(He). The idea of electron thermalization was motivated by the observation that much of the eKE distribution below IE(He) could be fit using the functional form for thermionic emission from a very cold cluster (T < 6 K).…”
Section: Discussionmentioning
confidence: 96%
See 1 more Smart Citation
“…The importance of Rydberg-like excitations in He droplets below IE(He) has been established in the fluorescence excitation spectra by Möller and co-workers, 53,55 and the role of molecular autoionizing states was first suggested by Fröchtenicht et al 9 to explain the onset of photoionization below IE(He). The idea of electron thermalization was motivated by the observation that much of the eKE distribution below IE(He) could be fit using the functional form for thermionic emission from a very cold cluster (T < 6 K).…”
Section: Discussionmentioning
confidence: 96%
“…Fröchtenicht et al 9 performed retarding field measurements of the cluster ion fragments following photoionization and showed that, under similar source conditions, the fragmentation process resulted in cluster ions with N + > 5 × 10 3 atoms. As we cannot effectively detect ions of this size, there is a disparity between the electron imaging and ion time-of-flight measurements.…”
Section: Discussionmentioning
confidence: 99%
“…It appears to be the same feature that was seen in our photoelectron images of pure He droplets. At 23.5 eV, 25 an energy below the ionization potential of atomic He (24.6 eV) but above the ionization threshold of He droplets (∼23 eV), 24 this was the only electron signal seen. It was also present in our photoelectron images of pure droplets above 24.6 eV, which were dominated by fast electrons from direct ionization of He atoms within the droplet.…”
Section: A Origins Of Features a And B: Penning Ionizationmentioning
confidence: 95%
“…24,26 The eKEs of the peaks comprising feature A show that the full excitation energy of 21.6 eV is available for reaction 1; that is, the 0.4 eV difference compared to the atomic transition is not dissipated in the droplet prior to dopant ionization. Instead, it is likely that a series of resonant excitation transfer collisions occurs within the droplet where the electronic excitation hops from one atom to another until a He atom adjacent to the dopant is excited, after which reaction 1 can proceed.…”
Section: A Origins Of Features a And B: Penning Ionizationmentioning
confidence: 99%
See 1 more Smart Citation